2006
DOI: 10.1016/j.otohns.2005.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Incidences of Obstructive Sleep Apnea‐Hypopnea Syndrome in African‐Americans versus Caucasian‐Americans

Abstract: B-3b.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 13 publications
(19 reference statements)
0
30
0
Order By: Relevance
“…Epidemiologic evidence shows that individuals of black race/ethnicity are three times as likely as those of white race/ethnicity to meet criteria for obstructive sleep apnea. [38][39][40] Individuals with obstructive sleep apnea, a condition that causes significant nocturnal sleep disturbances and excessive daytime sleepiness, have shown worse functional capacity than healthy controls. 41,42 Among 5,301 African American adults, a recent report from Jackson Heart study showed an independent association between sleep disordered breathing symptoms and sleep duration.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic evidence shows that individuals of black race/ethnicity are three times as likely as those of white race/ethnicity to meet criteria for obstructive sleep apnea. [38][39][40] Individuals with obstructive sleep apnea, a condition that causes significant nocturnal sleep disturbances and excessive daytime sleepiness, have shown worse functional capacity than healthy controls. 41,42 Among 5,301 African American adults, a recent report from Jackson Heart study showed an independent association between sleep disordered breathing symptoms and sleep duration.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] In either case, the low referral rate is particularly salient, as many non-Hispanic blacks, a high-risk group, may be less likely to be screened. 14 The foregoing evidence highlights the importance of OSA knowledge among providers, as OSA knowledge may be instrumental in evaluation and treatment of this condition. The purpose of this study was to assess knowledge and attitudes toward OSA among community physicians.…”
mentioning
confidence: 99%
“…Comparatively, estimates of daytime sleepiness in Sweden, France, and in the UK were 16%, 20%, and 15%, respectively [39,42,43]. Of particular interest is the observation that rates of daytime sleepiness among Caribbean-born blacks in our study were also higher than that generally observed for blacks (19%) [44], who typically experience more severe daytime sleepiness than do age-matched whites [18,34,35]. These findings support the notion that blacks in America do not constitute a homogenous group regarding snoring and daytime sleepiness, two of the most frequent symptoms of OSA.…”
Section: Discussionmentioning
confidence: 42%
“…Epidemiologic and clinical studies have shown that generally blacks are characterized by more severe sleep apnea compared with their white counterparts [18,[32][33][34][35]. Our study is the first to examine symptoms of OSA among Caribbean men and women residing in Brooklyn, NY.…”
Section: Discussionmentioning
confidence: 98%